2016
DOI: 10.1002/jcb.25664
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic Differentiation of Mesenchymal Stem Cells Induces Alterations in Extracellular Nucleotides Metabolism

Abstract: The presented results show for the first time that the neurogenic transdifferentiation of hUC-MSCs considerably changes the elements of purinergic signaling profile. Although, it has been demonstrated in the literature that extracellular nucleotides and nucleosides determine the fate of mesenchymal and neural stem cells, there is lack of comprehensive studies on the activity of ecto-enzymes metabolizing nucleotides on the surface of neurogenically induced cells. Our study shows that human UC-MSCs sense the mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…PSA NCAM and A2B5 are markers of neurogenesis as a marker of an immature neuron and glial cells. This is in accor dance with the previous research conducted by Czarnecka et al (2017), which states that MSCs from the human um bilical cord can differentiate into neurons and glial cells us ing commercial neuron mediums (MSC Neurogenic Dif ferentiation Medium) which produces NCAM+ (50,83 ± 3.01%) and A2B5+ (19.97 ± 1.70%). In this study, a de crease in the percentage of neuron and glial markers may be due to the differentiation of MSCs that are already in the mature neuron stage with positive MAP2 markers.…”
Section: Discussionsupporting
confidence: 89%
“…PSA NCAM and A2B5 are markers of neurogenesis as a marker of an immature neuron and glial cells. This is in accor dance with the previous research conducted by Czarnecka et al (2017), which states that MSCs from the human um bilical cord can differentiate into neurons and glial cells us ing commercial neuron mediums (MSC Neurogenic Dif ferentiation Medium) which produces NCAM+ (50,83 ± 3.01%) and A2B5+ (19.97 ± 1.70%). In this study, a de crease in the percentage of neuron and glial markers may be due to the differentiation of MSCs that are already in the mature neuron stage with positive MAP2 markers.…”
Section: Discussionsupporting
confidence: 89%
“…The ability of hMSCs to transdifferentiate into neurogenic lineage has been confirmed earlier by some authors [36][37][38]54,55] and this capacity has started recently to be investigated for hUC derived-MSCs [40][41][42][43]45,47]. In particular, human cord lining stem cells (hCL-MSCs) overcoming the preexisting difficulties inherent to MSCs from the bone marrow, offer not only a realistic, practical, and affordable alternative for tissue repair and regeneration [46], but also a promising cell-based model for in vitro screening and predictive studies for xenobiotic insults with particularly gained traction due to differentiation ability into several cell lineages including their potential towards converting into neural phenotypes [51,52].…”
Section: Discussionmentioning
confidence: 64%
“…Among the various sources-derived MSCs, those derived from the human umbilical cord (hUC-MSCs) have the advantages of simple convenient preparation, feasible source, non-traumatic risk of infection, more primitive properties, higher proliferation capacity, and their low immunogenicity and immunosuppressive characteristics turn hUC-MSCs to be an ideal source used as engineering cells in studying stem cell differentiation [40]. Recent investigations have demonstrated that MSCs derived from human umbilical cord can be most efficiently differentiated in vitro into cells of nonmesodermal origin including neuronal-like cells using specific induction protocols [40][41][42][43][44][45]. MSCs can be obtained from different compartments of the umbilical cord (UC) including the UC lining membrane (hCL-MSCs) [45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…Different studies performed in vivo and in vitro in recent years have demonstrated that MSCs release ATP and nucleosides constitutively or in response to mechanical or chemical stimulation [21]. Moreover, MSCs are sensitive to these purinergic signaling effectors due to their broad expression of purinergic receptors on their plasma membranes, including ATP and ADP receptors [10,13,16,17,48,49]. In fact, both ATP and adenosine are involved in the immunomodulatory capacity and in the lineage commitment of the MSCs.…”
Section: Discussionmentioning
confidence: 99%